Serous tubal intraepithelial carcinoma: an incidental finding in laparotomy for tubo-ovarian mass in woman aged 35 years - Kumari, Rinku; Sharma, Mamta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Serous tubal intraepithelial carcinoma (STIC) is a precursor lesion for high-grade pelvic serous carcinoma. The incidence of STIC is estimated to occur in 0.6% to 6% of women who are BRCA positive or have a strong family history of breast or ovarian cancer. We report a rare case of serous tubal Intraepithelial carcinoma in young woman undergoing laparotomy for tubo-ovarian mass who diagnosed STIC on histopathological examination of specimen. Women diagnosed incidentally at surgery for benign condition should be considered for repeat surgical staging. Etiology and management are similar to epithelial ovarian cancer but stage at diagnosis, lymphatic spread and overall survival appear to be different.